Multi-step pre-treatment of rice husk for fractionation of components including silica - Ishida, Shinnosuke; Kudo, Shinji; Asano, Shusaku; Hayashi, Jun-ichiro (Frontiers in Chemistry, 2025)
IntroductionRice husk, a widely available agricultural by-product lignocellulosic biomass, is a promising and sustainable feedstock for organic and inorganic chemicals due to the rich silica content. However, its current application is largely limited, with most being incinerated as waste. This study introduces a novel multi-step pre-treatment process to fractionate these components efficiently, enabling their comprehensive valorization.MethodsThe process begins with hydrothermal treatment, selectively extracting hemicellulose while preserving the structural integrity of other components. This is followed by an organosolv treatment using ethanol/water mixture, optimized to dissolve and extract organosolv lignin effectively. Subsequently, alkaline aqueous solution treatment under nitrogen atmosphere facilitates the recovery of silica as sodium silicate, a valuable industrial precursor. To ensure high-purity cellulose recovery, the final step employs alkaline hydrothermal processing under oxygen, achieving effective lignin depolymerization and removal.Results and discussionEach step was carefully optimized, considering parameters such as temperature, solvent composition, and reaction time, to enhance selectivity and yield. Notably, this method reduces environmental negative impact by avoiding the use of acids while utilizing renewable solvents. The sequential application of these treatments resulted in separation exceeding 97% for hemicellulose, lignin, and silica, leaving high-purity cellulose with the loss of 22.8 wt%. Hemicellulose, organosolv lignin, and silica in the removed fractions were 66.5, 78.1, and 77.5 wt% at the first, second, and third treatments, respectively.